Machine learning in the prediction, determination and further study of different cyber-attacks - Bansal, Sagar; Singh, Anshika (International Journal of Computer Sciences and Engineering, 2019)
Cyber Security introduces a group of methods, used to shield networks, data and programs from intrusion, deterioration and illegal access. Cyber intrusion is the act of breaking the security of one’s computer with the means of a network. To cut down the threat of various illegal accessing in order to enhance the cyber security, Machine Learning approach is used widely. Machine learning in itself is the study of various ways to train the machine with real datasets and make them act like humans in similar circumstances. In this paper, most of the Machine Learning and Deep Learning algorithms that are used for enhancing cyber security have been summed up.